Uji Toksisitas Ekstrak Etanol Kulit Buah Kopi Arabika (Coffea arabica L.) dan Bawang Dayak (Eleutherine palmifolia L.) dengan Metode Brine Shrimp Lethality (BSLT) - Fitri, Husna; Maliza, Rita; Refiani, Era; Laila, Alfiatul; Widyaningrum, Melinda (Journal Galung Tropika, 2021)
Coffee husk (Coffea arabica L.) and Dayak onion (Eleutherine palmifolia L.) are Indonesian endemic plants. This plant contains flavonoid compounds, tannins, caffeine, and polyphenols. Based on previous research, these compounds have antioxidants, anti-inflammatory, anti-bacterial properties for treating tumors, inflammation, and anti-cancer. This study aimed to determine the toxicity activity of Dayak coffee and onion peel extract on the mortality of shrimp larvae (Artemia salina Leach) using the Brine Shrimp Lethality Test (BSLT) method and variations in concentration (ppm), namely 0, 20, 50, 100, 250, 500, and 1000 ppm. The results of the BSLT test showed that the coffee peel extract had an LC50 value of 51.7369 ppm and the Dayak onion had an LC50 value of 70.9741 ppm. This result shows that the extracts of coffee skin and Dayak Onion are toxic because they can kill 50% of shrimp larvae. This research is a preliminary study to analyze the toxicity of the active compounds of natural ingredients. This study showed that coffee peel extract had better toxic activity against shrimp larvae mortality than Dayak onion extract.